Environmentally friendly sealant and preparation method thereof
By using modified white carbon black and composite flame retardant in environmentally friendly sealants, combined with the use of crosslinking agents and coupling agents, the problem of poor flame retardant and fire-retardant effects of existing environmentally friendly sealants is solved, and higher mechanical strength and adhesive properties are achieved, and good high temperature and mildew resistance are achieved.
Patent Information
- Application Number
- CN202211593780.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The existing environmentally friendly sealants are relatively lacking in flame retardant and fire-retardant effects, and have poor mechanical strength and adhesive properties.
Modified white carbon black is used as a filler and combined with a composite flame retardant. Through the combination of crosslinking agent and coupling agent, the crosslinking depth of silicone deep sealant is deepened and the compatibility, mechanical and adhesive properties of the material are improved.
It significantly improves the flame retardant properties and mechanical strength of environmentally friendly sealants, while maintaining good bonding properties and high temperature resistance and mildew resistance.
Smart Images

Figure BDA0003996037040000121 
Figure BDA0003996037040000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealant or adhesive connection, and in particular to an environmentally friendly sealant and a preparation method thereof. Background Art
[0002] There are many types of sealants, including environmentally friendly sealants, polyurethane sealants, acrylic sealants, PVC sealants, epoxy sealants, butyl sealants, chloroprene sealants, etc. It is an adhesive used to fill the gap of the configuration to play a sealing role. It has the functions of leak prevention, waterproofing, vibration prevention, sound insulation, heat insulation, etc., and is widely used in the sealing of construction, transportation, electronic instruments, and parts. Chinese patent CN108997945A discloses an environmentally friendly sealant and a preparation method thereof, which includes the following raw materials: methyl dimethoxysilane end-capped polyether, aminosilane coupling agent, fumed silica, nano calcium carbonate, cross-linking agent, hindered amine stabilizer. The environmentally friendly sealant of the present invention has low VOC emission during curing, does not add white oil, phthalate plasticizer, and will not cause the problem of plasticizer migration and contamination of the substrate surface. It is safe and environmentally friendly, but the flame retardant and fireproof effect of the sealant is poor. Chinese patent CN107686709A discloses an environmentally friendly sealant and a preparation method thereof, which is composed of the following raw materials: vulcanized silicone rubber, modified polypropylene resin, epoxy resin, titanium dioxide, ethylenediaminetetraacetic acid, tea polyphenols, triethylenediamine, dimethyl silicone oil, talcum powder, sorbic acid, and ethanol. The sealant of the invention is non-toxic and harmless, green and environmentally friendly, has a good sealing effect and high viscosity, but the mechanical strength and flame retardancy of the sealant are poor. Summary of the invention
[0003] In view of the above-mentioned defects in the prior art, the present invention provides an environmentally friendly sealant and a preparation method thereof.
[0004] The environmentally friendly sealant comprises the following components in parts by weight: 50 to 70 parts of 107 silicone rubber, 20 to 50 parts of plasticizer, 10 to 20 parts of modified white carbon black, 1 to 5 parts of flame retardant, 2 to 10 parts of cross-linking agent, 0.5 to 4 parts of coupling agent and 1 to 5 parts of catalyst.
[0005] Preferably, 1 to 3 parts of anti-mildew compound are also included.
[0006] 107 silicone rubber is α, ω-dihydroxy polysiloxane, which is the base rubber of two-component and one-component condensation silicone rubber. The raw rubber can be used directly as a commodity and can be used as an intermediate to produce various condensation silicone rubber products. Its chemical name is hydroxyl-terminated polydimethylsiloxane, which is a colorless, transparent, flowing liquid. In addition to the general properties of methyl silicone oil, it also has the reactivity of hydroxyl, excellent electrical insulation and high and low temperature resistance, high flash point, low freezing point, and can be used for a long time under -50℃ ~ 250℃ conditions. It has a small viscosity-stability coefficient, a large compression rate, low surface tension, and good hydrophobicity and moisture resistance.
[0007] The plasticizer is one or a mixture of two or more of 201 methyl silicone oil, white oil, and epoxy soybean oil; preferably, the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil, and the mass ratio of the two is 2 to 3:1.
[0008] 201 methyl silicone oil, whose Chinese name is polydimethylsiloxane and English name is Dimethy silicone oil 201, is a transparent, colorless, odorless, non-toxic oily liquid with the characteristics of high and low temperature resistance. It can be used for a long time at -50 ~ 180 ℃, and the long-term use temperature can reach 200 ℃ in air-isolated or in inert gas. It has very small surface silicon tension, high compression rate, good shear resistance, small viscosity-temperature coefficient, and small dielectric loss; it is resistant to arc and corona, non-flammable; it is hydrophobic and moisture-proof, and has good physiological inertness.
[0009] White carbon black: amorphous silicon dioxide, also known as hydrated silicon dioxide, has a molecular structure of SiO2·nH2O. It is a white, non-toxic, amorphous powder. White carbon black is divided into two categories: fumed white carbon black and precipitated white carbon black due to different preparation methods. The surface of fumed SiO2 particles is usually rich in silanol groups. These silanol groups easily absorb moisture in the air, causing SiO2 to form secondary aggregates, making it difficult to disperse evenly in the matrix. In order to weaken its adsorption and enhance its compatibility with the rubber matrix, it is necessary to modify the fumed SiO2.
[0010] The technical concept of the present invention is: using modified white carbon black as a filler and adding it to the base material, and using it in combination with a composite flame retardant, effectively improving the flame retardant properties of the environmentally friendly sealant, and using a cross-linking agent and a coupling agent in combination is beneficial to deepening the cross-linking depth of the silicone deep sealant, and using it in combination with a plasticizer and a silane coupling agent to improve the compatibility, mechanical and bonding properties of various materials.
[0011] The modified white carbon black preparation method comprises the following steps:
[0012] (1) By weight, 0.05-0.1 parts of sodium dodecyl sulfate and 1-3 parts of gas-phase SiO2 are added to an aqueous solution of 50-90 parts of ethanol, stirred evenly, and ultrasonicated for 0.5-1 hour, and then heated to 50-80° C., and then 0.5-1 parts of γ-methacryloxypropyltrimethoxysilane are added dropwise to the reaction solution, and the reaction is continued at a constant temperature for 2-4 hours, and then washed with ethanol, and centrifuged to obtain KH570-SiO2;
[0013] (2) KH570-SiO2 is placed in an ethanol solution, into which 0.1 to 0.3 parts of hydroxy silicone oil and 1 to 2 parts of dibutyltin dilaurate are added dropwise, and after stirring at 10 to 40° C. for 2 to 6 hours, the solution is washed with ethanol and centrifuged to obtain modified silica.
[0014] The particle size of the modified white carbon black is 20-30 nm. The modified white carbon black is well dispersed, which greatly changes the inherent hydrophilicity of the surface of the white carbon black, has a good reinforcing effect on the environmentally friendly sealant, and improves the mechanical properties of the material.
[0015] The flame retardant is one or two or a mixture of two or more of Mg(OH)2 powder, modified Mg(OH)2, triethyl phosphate, silicone powder, triphenyl phosphate, tributyl phosphate, ammonium polyphosphate, and melamine; the preferred flame retardant is a mixture of modified Mg(OH)2 powder and triethyl phosphate, and the mass ratio of the two is 1 to 3:1.
[0016] Mg(OH)2 powder is a halogen-free, low-smoke, non-toxic, environmentally friendly flame retardant with good flame retardant effect, but the large amount added has a great negative impact on the mechanical properties of the sealant. Therefore, it is very necessary to ultra-fine it and surface treat it. The modified Mg(OH)2 is more evenly distributed in the rubber matrix, which improves the hydrophilicity of the surface of the magnesium hydroxide particles, enhances its lipophilicity, obtains a stronger bonding interface phase, avoids defects caused by agglomeration, and thus improves the mechanical properties.
[0017] The preparation method of the modified Mg(OH)2 is as follows: by weight, 500-600 parts of water, 30-60 parts of ethanol, and 20-30 parts of aluminate coupling agent are added to a reaction kettle, stirred and heated to 50-80°C, 250-300 parts of Mg(OH)2 are added and continued to stir for 20-40 minutes under N2 protection, 15-20 parts of butyl acrylate and 0.3-0.6 parts of initiator azobisisobutyronitrile are added to react for 0.5-2 hours, 15-20 parts of methyl methacrylate and 1-2 parts of initiator azobisisobutyronitrile are added to continue to react for 2-4 hours, after the reaction is completed, the modified Mg(OH)2 is purified by a Soxhlet extractor at 60-100°C for 12-24 hours, and then dried at 50-80°C to obtain the modified Mg(OH)2.
[0018] The crosslinking agent is one or more of methyltributylacetoximine silane, vinyltributylacetoximine silane, methyltrimethoxysilane, ethyltrimethoxysilane and methyltriacetoxysilane.
[0019] The coupling agent is one or two or a mixture of two or more of γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane.
[0020] The catalyst is one or two or a mixture of two or more of dibutyltin dilaurate, dihexyltin dilaurate, dibutyltin diacetate, dihexyltin diacetate, isopropyl titanate and butyl titanate.
[0021] The preparation method of the mildew-proof composite is as follows:
[0022] The method comprises the following steps: adding 12 to 18 parts of 1-bromomethylnaphthalene to 20 to 50 parts of methanol by weight, stirring at 70 to 80° C. for 1 to 3 minutes; adding 50 to 70 parts of a 20 to 30 wt% polyhexamethylene guanidine phosphate aqueous solution at a rate of 1 to 2 mL / min, continuing stirring for 8 to 15 minutes after the addition is completed, filtering and drying to obtain a modified guanidine salt; adding 0.5 to 0.8 parts of the modified guanidine salt, 0.3 to 0.5 parts of pyraclostrobin, 1 to 2 parts of nano titanium dioxide and 0.5 to 1 part of nano boron nitride to 10 to 30 parts of dioctyl terephthalate, performing ultrasonic treatment for 1 to 2 hours, centrifuging and drying to obtain the anti-mildew composite.
[0023] The invention also discloses a method for preparing the environmentally friendly sealant, comprising the following steps:
[0024] S1 weighs 50-70 parts of 107 silicone rubber, 20-50 parts of plasticizer, 10-20 parts of modified white carbon black, 1-5 parts of flame retardant, 0.5-4 parts of coupling agent, and 1-5 parts of catalyst, adds them to a kneader, stirs for 3-5 hours at 80-120°C and vacuum degree -0.06--0.1MPa, and then grinds to obtain powder;
[0025] S2. After the powder obtained in step S1 is cooled to 30-60° C., the powder is added into a disperser, 2-10 parts of a cross-linking agent are added, and stirring is continued for 20-40 minutes under a vacuum degree of -0.06 to -0.1 MPa, and the environmentally friendly flame-retardant and environmentally friendly sealant is obtained by discharging and packaging.
[0026] Preferably, the step S1 further comprises 1 to 3 portions of anti-mildew compound.
[0027] Beneficial effects of the present invention: The environmentally friendly sealant prepared by the present invention is green and environmentally friendly, has excellent bonding performance and mechanical strength, and also has the ability of mildew resistance, high temperature resistance, flame retardancy and fire prevention. Among them, the composite use of inorganic powder flame retardant and liquid halogen-free flame retardant in a specific ratio not only has a small amount of addition, but also ensures the mechanical properties and bonding properties of the sealant while improving the flame retardancy. In addition, the modification of white carbon black overcomes the disadvantages of its large surface energy and easy agglomeration, so that the modified white carbon black can be well dispersed in the environmentally friendly sealant, has a good reinforcing effect on the environmentally friendly sealant, and improves the mechanical properties of the material. DETAILED DESCRIPTION
[0028] The present invention is further described in detail with reference to the following specific embodiments. The process, conditions, experimental methods, etc. for implementing the invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention has no special restrictions.
[0029] 107 silicone rubber, purchased from Shandong Guohua Chemical Co., Ltd., has the appearance of colorless viscous liquid, the model is industrial grade, the viscosity (25°C, cs) is 25-35, the volatile matter (150°C×3h, %): ≤2, and the surface curing time (h) ≤2.
[0030] 201 methyl silicone oil was purchased from Jinan Huijinchuan Chemical Co., Ltd., with a content of 99.9% and an appearance of a colorless transparent liquid.
[0031] Epoxidized soybean oil was purchased from Wuhan Xindongyi Chemical Co., Ltd. It has a light yellow oily liquid appearance, an epoxy value of 6.1%, an acid value (mgkOH / g) ≤ 0.8, and an iodine value (g12 / 100g) % ≤ 3.
[0032] Gas-phase SiO2 was purchased from Shanghai Kaiyin Chemical Co., Ltd., model AEROSIL R106.
[0033] Mg(OH)2 powder was purchased from Weifang Lihe Powder Technology Co., Ltd. It has the appearance of white powder, a content of 99%, whiteness ≤98, moisture content (%) ≤0.2±0.1, and particle size D50 (um) ≤3.
[0034] KH570, 3-(methacryloyloxy)propyltrimethoxysilane, was purchased from Guangzhou Kangou Shuang Trading Co., Ltd., with an active substance content of 97%.
[0035] Aluminate coupling agent was purchased from Shandong Guohua Chemical Co., Ltd. It has the appearance of white crystals and is of industrial grade.
[0036] Comparative Example
[0037] The preparation method of environmentally friendly sealant is as follows:
[0038] S1 weighed 60g 107 silicone rubber, 40g plasticizer, 15g white carbon black, 5g flame retardant, 1g γ-aminopropyltriethoxysilane, and 3g dibutyltin dilaurate, added to a kneader, stirred at 100°C and vacuum degree -0.07MPa for 4 hours, and then ground to obtain a powder;
[0039] S2: After the powder obtained in step S1 is cooled to 30°C, the powder is added to a high-speed disperser, 8g of methyl tributylidene silane is added, and stirring is continued for 30 minutes under a vacuum degree of -0.07MPa, and the environmentally friendly sealant is obtained by discharging and packaging; the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil in a mass ratio of 2:1; the flame retardant is Mg(OH)2 powder.
[0040] Example 1
[0041] The preparation method of environmentally friendly sealant is as follows:
[0042] S1 weighed 60g 107 silicone rubber, 40g plasticizer, 15g modified white carbon black, 5g flame retardant, 1g γ-aminopropyltriethoxysilane, and 3g dibutyltin dilaurate, added to a kneader, stirred at 100°C and vacuum degree -0.07MPa for 4 hours, and then ground to obtain a powder;
[0043] S2: After the powder obtained in step S1 is cooled to 30°C, the powder is added to a high-speed disperser, 8g of methyl tributylidene silane is added, and stirring is continued for 30 minutes under a vacuum degree of -0.07MPa, and the environmentally friendly sealant is obtained by discharging and packaging; the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil in a mass ratio of 2:1; the flame retardant is Mg(OH)2 powder.
[0044] The preparation method of the modified white carbon black is as follows:
[0045] (1) 0.08 g of sodium dodecyl sulfate and 2 g of gas-phase SiO2 were added to 60 mL of aqueous solution containing 30 mL of ethanol, stirred evenly and ultrasonicated for 0.5 hours, then heated to 70°C, and then 0.8 g of γ-methacryloxypropyltrimethoxysilane was added dropwise to the reaction solution. After constant temperature reaction for 3 hours, the solution was washed with ethanol and centrifuged to obtain KH570-SiO2;
[0046] (2) KH570-SiO2 was placed in an ethanol solution, into which 0.2 g of hydroxy silicone oil and 1 g of dibutyltin dilaurate were added dropwise. After stirring at 25°C for 5 hours, the solution was washed with ethanol and centrifuged to obtain modified silica.
[0047] Example 2
[0048] The preparation method of environmentally friendly sealant is as follows:
[0049] S1 weighed 60g 107 silicone rubber, 40g plasticizer, 15g modified white carbon black, 5g flame retardant, 1g γ-aminopropyltriethoxysilane, and 3g dibutyltin dilaurate, added to a kneader, stirred at 100°C and vacuum degree -0.07MPa for 4 hours, and then ground to obtain a powder;
[0050] S2: After the powder obtained in step S1 is cooled to 30°C, the powder is added to a high-speed disperser, 8g of methyl tributylidene silane is added, and stirring is continued for 30 minutes under a vacuum degree of -0.07MPa, and the environmentally friendly sealant is obtained by discharging and packaging; the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil in a mass ratio of 2:1; the flame retardant is triethyl phosphate.
[0051] The preparation method of the modified white carbon black is as follows:
[0052] (1) 0.08 g of sodium dodecyl sulfate and 2 g of gas-phase SiO2 were added to 60 mL of aqueous solution containing 30 mL of ethanol, stirred evenly and ultrasonicated for 0.5 hours, then heated to 70°C, and then 0.8 g of γ-methacryloxypropyltrimethoxysilane was added dropwise to the reaction solution. After constant temperature reaction for 3 hours, the solution was washed with ethanol and centrifuged to obtain KH570-SiO2;
[0053] (2) KH570-SiO2 was placed in an ethanol solution, into which 0.2 g of hydroxy silicone oil and 1 g of dibutyltin dilaurate were added dropwise. After stirring at 25°C for 5 hours, the solution was washed with ethanol and centrifuged to obtain modified silica.
[0054] Example 3
[0055] The preparation method of environmentally friendly sealant is as follows:
[0056] S1 weighed 60g 107 silicone rubber, 40g plasticizer, 15g modified white carbon black, 5g flame retardant, 1g γ-aminopropyltriethoxysilane, and 3g dibutyltin dilaurate, added to a kneader, stirred at 100°C and vacuum degree -0.07MPa for 4 hours, and then ground to obtain a powder;
[0057] S2: After the powder obtained in step S1 is cooled to 30°C, the powder is added to a high-speed disperser, 8g of methyl tributylidene silane is added, and stirring is continued for 30 minutes under a vacuum degree of -0.07MPa, and the environmentally friendly sealant is obtained by discharging and packaging; the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil in a mass ratio of 2:1; the flame retardant is modified Mg(OH)2.
[0058] The preparation method of the modified white carbon black is as follows:
[0059] (1) 0.08 g of sodium dodecyl sulfate and 2 g of gas-phase SiO2 were added to 60 mL of aqueous solution containing 30 mL of ethanol, stirred evenly and ultrasonicated for 0.5 hours, then heated to 70°C, and then 0.8 g of γ-methacryloxypropyltrimethoxysilane was added dropwise to the reaction solution. After constant temperature reaction for 3 hours, the solution was washed with ethanol and centrifuged to obtain KH570-SiO2;
[0060] (2) KH570-SiO2 was placed in an ethanol solution, into which 0.2 g of hydroxy silicone oil and 1 g of dibutyltin dilaurate were added dropwise. After stirring at 25°C for 5 hours, the solution was washed with ethanol and centrifuged to obtain modified silica.
[0061] The preparation method of the modified Mg(OH)2 is as follows: weigh 590g of water, 50g of ethanol, and 24g of aluminate coupling agent in a reactor, stir for 10min, heat to 60°C, then evacuate the air from the reactor, fill with N2 for protection, add 260g of Mg(OH)2 under N2 protection, continue stirring for 30min, then add 16g of butyl acrylate and 0.5g of azobisisobutyronitrile to react for 1 hour; add 16g of methyl methacrylate and 1g of azobisisobutyronitrile to the reaction solution and continue to react for 3 hours. After the reaction is completed, use 100mL of ethanol as a solvent, purify with a Soxhlet extractor at 80°C for 24 hours, and then dry the obtained solid in a vacuum drying oven at 70°C to obtain the modified Mg(OH)2.
[0062] Example 4
[0063] The preparation method of environmentally friendly sealant is as follows:
[0064] S1 weighed 60g 107 silicone rubber, 40g plasticizer, 15g modified white carbon black, 5g flame retardant, 1g γ-aminopropyltriethoxysilane, and 3g dibutyltin dilaurate, added to a kneader, stirred at 100°C and vacuum degree -0.07MPa for 4 hours, and then ground to obtain a powder;
[0065] S2: After the powder obtained in step S1 is cooled to 30°C, the powder is added to a high-speed disperser, 8g of methyl tributylidene silane is added, and stirring is continued for 30 minutes under a vacuum degree of -0.07MPa, and the environmentally friendly sealant is obtained by discharging and packaging; the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil in a mass ratio of 2:1; the flame retardant is a mixture of modified Mg(OH)2 and triethyl phosphate in a mass ratio of 1:2.
[0066] The preparation method of the modified white carbon black is as follows:
[0067] (1) 0.08 g of sodium dodecyl sulfate and 2 g of gas-phase SiO2 were added to 60 mL of aqueous solution containing 30 mL of ethanol, stirred evenly and ultrasonicated for 0.5 hours, then heated to 70°C, and then 0.8 g of γ-methacryloxypropyltrimethoxysilane was added dropwise to the reaction solution. After constant temperature reaction for 3 hours, the solution was washed with ethanol, centrifuged, and the precipitate was dried to obtain KH570-SiO2;
[0068] (2) KH570-SiO2 was placed in an ethanol solution, to which 0.2 g of hydroxy silicone oil and 1 g of dibutyltin dilaurate were added dropwise. After stirring at 25°C for 5 hours, the solution was washed with ethanol and centrifuged. The precipitate was dried to obtain modified silica.
[0069] The preparation method of the modified Mg(OH)2 is as follows: weigh 590g of water, 50g of ethanol, and 24g of aluminate coupling agent in a reactor, stir for 10min, heat to 60°C, then evacuate the air from the reactor, fill with N2 for protection, add 260g of Mg(OH)2 under N2 protection, continue stirring for 30min, then add 16g of butyl acrylate and 0.5g of azobisisobutyronitrile to react for 1 hour; add 16g of methyl methacrylate and 1g of azobisisobutyronitrile to the reaction solution and continue to react for 3 hours. After the reaction is completed, use 100mL of ethanol as a solvent, purify with a Soxhlet extractor at 80°C for 24 hours, and then dry the obtained solid in a vacuum drying oven at 70°C to obtain the modified Mg(OH)2.
[0070] Example 5
[0071] The preparation method of environmentally friendly sealant is as follows:
[0072] S1 weighed 60g 107 silicone rubber, 40g plasticizer, 15g modified white carbon black, 5g flame retardant, 2.5g mildew-proof compound, 1g γ-aminopropyltriethoxysilane, 3g dibutyltin dilaurate, added to a kneader, stirred at 100°C and vacuum degree -0.07MPa for 4 hours, and then ground to obtain powder;
[0073] S2: After the powder obtained in step S1 is cooled to 30°C, the powder is added to a high-speed disperser, 8g of methyl tributylidene silane is added, and stirring is continued for 30 minutes under a vacuum degree of -0.07MPa, and the environmentally friendly sealant is obtained by discharging and packaging; the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil in a mass ratio of 2:1; the flame retardant is a mixture of modified Mg(OH)2 and triethyl phosphate in a mass ratio of 1:2.
[0074] The preparation method of the modified white carbon black is as follows:
[0075] (1) 0.08 g of sodium dodecyl sulfate and 2 g of gas-phase SiO2 were added to 60 mL of aqueous solution containing 30 mL of ethanol, stirred evenly and ultrasonicated for 0.5 hours, then heated to 70°C, and then 0.8 g of γ-methacryloxypropyltrimethoxysilane was added dropwise to the reaction solution. After constant temperature reaction for 3 hours, the solution was washed with ethanol, centrifuged, and the precipitate was dried to obtain KH570-SiO2;
[0076] (2) KH570-SiO2 was placed in an ethanol solution, to which 0.2 g of hydroxy silicone oil and 1 g of dibutyltin dilaurate were added dropwise. After stirring at 25°C for 5 hours, the solution was washed with ethanol and centrifuged. The precipitate was dried to obtain modified silica.
[0077] The preparation method of the modified Mg(OH)2 is as follows: weigh 590g of water, 50g of ethanol, and 24g of aluminate coupling agent in a reactor, stir for 10min, heat to 60°C, then evacuate the air from the reactor, fill with N2 for protection, add 260g of Mg(OH)2 under N2 protection, continue stirring for 30min, then add 16g of butyl acrylate and 0.5g of azobisisobutyronitrile to react for 1 hour; add 16g of methyl methacrylate and 1g of azobisisobutyronitrile to the reaction solution and continue to react for 3 hours. After the reaction is completed, use 100mL of ethanol as a solvent, purify with a Soxhlet extractor at 80°C for 24 hours, and then dry the obtained solid in a vacuum drying oven at 70°C to obtain the modified Mg(OH)2.
[0078] The mildew-proof compound is a mixture of nano titanium dioxide and nano boron nitride in a mass ratio of 1.2:0.8. Among them, nano titanium dioxide, 10nm, is from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; nano boron nitride, 500nm, is from Shandong Zhongtu Chemical Co., Ltd. The mildew-proof performance of the environmentally friendly sealant obtained in Example 5 was evaluated with reference to GB / T 1741-2020. After 3 months, the mildew-proof grade of Example 5 was Grade 1.
[0079] Example 6
[0080] The preparation method of environmentally friendly sealant is as follows:
[0081] S1 weighed 60g 107 silicone rubber, 40g plasticizer, 15g modified white carbon black, 5g flame retardant, 2.5g mildew-proof compound, 1g γ-aminopropyltriethoxysilane, 3g dibutyltin dilaurate, added to a kneader, stirred at 100°C and vacuum degree -0.07MPa for 4 hours, and then ground to obtain powder;
[0082] S2: After the powder obtained in step S1 is cooled to 30°C, the powder is added to a high-speed disperser, 8g of methyl tributylidene silane is added, and stirring is continued for 30 minutes under a vacuum degree of -0.07MPa, and the environmentally friendly sealant is obtained by discharging and packaging; the plasticizer is a mixture of 201 methyl silicone oil and epoxy soybean oil in a mass ratio of 2:1; the flame retardant is a mixture of modified Mg(OH)2 and triethyl phosphate in a mass ratio of 1:2.
[0083] The preparation method of the modified white carbon black is as follows:
[0084] (1) 0.08 g of sodium dodecyl sulfate and 2 g of gas-phase SiO2 were added to 60 mL of aqueous solution containing 30 mL of ethanol, stirred evenly and ultrasonicated for 0.5 hours, then heated to 70°C, and then 0.8 g of γ-methacryloxypropyltrimethoxysilane was added dropwise to the reaction solution. After constant temperature reaction for 3 hours, the solution was washed with ethanol, centrifuged, and the precipitate was dried to obtain KH570-SiO2;
[0085] (2) KH570-SiO2 was placed in an ethanol solution, to which 0.2 g of hydroxy silicone oil and 1 g of dibutyltin dilaurate were added dropwise. After stirring at 25°C for 5 hours, the solution was washed with ethanol and centrifuged. The precipitate was dried to obtain modified silica.
[0086] The preparation method of the modified Mg(OH)2 is as follows: weigh 590g of water, 50g of ethanol, and 24g of aluminate coupling agent in a reactor, stir for 10min, heat to 60°C, then evacuate the air from the reactor, fill with N2 for protection, add 260g of Mg(OH)2 under N2 protection, continue stirring for 30min, then add 16g of butyl acrylate and 0.5g of azobisisobutyronitrile to react for 1 hour; add 16g of methyl methacrylate and 1g of azobisisobutyronitrile to the reaction solution and continue to react for 3 hours. After the reaction is completed, use 100mL of ethanol as a solvent, purify with a Soxhlet extractor at 80°C for 24 hours, and then dry the obtained solid in a vacuum drying oven at 70°C to obtain the modified Mg(OH)2.
[0087] The preparation method of the mildew-proof composite is as follows:
[0088] Take 15g of 1-bromomethylnaphthalene and add it to 30mL of methanol, stir at 75°C for 2min; then add 60mL of 25wt% polyhexamethyleneguanidine phosphate aqueous solution at a rate of 1.5mL / min, continue stirring for 10min after the addition is complete, filter and dry to obtain modified guanidine salt; add 0.6g of modified guanidine salt, 0.4g of pyraclostrobin, 1.2g of nano titanium dioxide, and 0.8g of nano boron nitride to 20mL of dioctyl terephthalate for ultrasonic treatment for 2h, centrifuge and dry to obtain the anti-mildew composite. Among them, nano titanium dioxide, 10nm, Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; nano boron nitride, 500nm, Shandong Zhongtu Chemical Co., Ltd. The anti-mildew performance of the environmentally friendly sealant obtained in Example 6 was evaluated with reference to GB / T1741-2020. After 3 months, the anti-mildew grade of Example 6 was 0.
[0089] Test Example 1
[0090] The environmentally friendly sealants prepared in the comparative example and embodiments 1-4 were used as test objects, and performance tests were performed on them. The test conditions were standard conditions, with a temperature of 23±1° C. and a humidity of 50%±5%.
[0091] Flame retardant performance test: The test was conducted according to the vertical method standard in GB / T2408-2008 Determination of Horizontal and Vertical Methods for Combustion Performance of Plastics. Five specimens of the environmentally friendly sealants prepared in the comparative example and Examples 1-4 were prepared with the size of (125±5) mm×(13.0±0.3) mm×(3.0±0.2) mm, and then cured for 14 days under standard test conditions for the experiment.
[0092] Table 1: Flame retardant performance test of environmentally friendly sealant
[0093]
[0094] Note: The flame retardant grade increases from HB, V-2, V-1 to V-0:
[0095] 1. HB: The lowest flame retardant grade in the UL94 standard. It requires that for samples with a thickness of 3 to 13 mm, the burning speed is less than 40 mm per minute; for samples with a thickness of less than 3 mm, the burning speed is less than 70 mm per minute; or it will be extinguished before the 100 mm mark.
[0096] 2. V-2: After two 10-second combustion tests on the sample, the flame goes out within 60 seconds. Burning objects may fall off.
[0097] 3. V-1: After two 10-second combustion tests on the sample, the flame goes out within 60 seconds. No burning objects can fall.
[0098] 4. V-0: After two 10-second combustion tests on the sample, the flame goes out within 30 seconds. No burning objects can fall.
[0099] Test Example 2
[0100] Mechanical properties test: After the environmentally friendly sealants prepared in the comparative example and Examples 1-4 were stored in a sealed container at 70°C for 5 days, 2 mm thick test pieces were made at 20°C and 60% RH. After curing for 168 hours under the same environment, the mechanical properties of the test pieces were tested according to the method in GB16776-2005 Silicone Structural Sealant for Buildings. The test method is:
[0101] Surface drying time: Surface drying time test: According to the experimental steps of Method A in Article 8.1 of GB / T13477.5-2002 Test Methods for Building Sealing Materials Part 5: Determination of Surface Drying Time, the prepared specimen is left to stand for a certain period of time under standard conditions, and then a polyethylene film is placed at 1 / 2 of the longitudinal position of the specimen surface, and a brass plate is placed at the center of the film. After 30 seconds, the brass plate is removed, and the film is peeled off from the specimen surface at a 90° angle at a uniform speed of 15 seconds. Repeat the above operation at other locations at appropriate intervals until no specimen adheres to the polyethylene strip. Record the time from the specimen being formed to the specimen no longer adhering to the polyethylene strip.
[0102] Tensile bond strength: The test is carried out in accordance with GB / T 13477.8-2017 Test methods for building sealing materials Part 8: Determination of tensile adhesion, with a speed of 6 mm / mm.
[0103] The elongation at break is tested according to “GB / T13477.8-2017 Test Methods for Building Sealing Materials Part 8: Determination of Tensile Adhesion”.
[0104] Table 2: Mechanical properties test of environmentally friendly sealants
[0105]
[0106] The present invention prepares a high-temperature resistant filler and a composite flame retardant. The flame retardant is formed by compounding modified Mg(OH)2 and liquid phosphorus-based flame retardant triethyl phosphate in a certain mass ratio. The flame retardant can form a continuous, dense and stable carbonization layer during high-temperature combustion, reduce smoke generation and combustible droplets. The surface of the high-temperature resistant filler-modified white carbon black is a network structure with hydrophobicity, which can inhibit colloid flow, accelerate curing, shorten surface drying time, and improve bonding effect. When mixed with the composite flame retardant, the polymer molecules are bound between layers, limiting the free movement of molecular chains and short chains, thereby improving the sealing and high temperature resistance of the environmentally friendly sealant.
Claims
1. Sealant, characterized in that: The invention comprises the following components in parts by weight: 50-70 parts of 107 silicone rubber, 20-50 parts of plasticizer, 10-20 parts of modified white carbon black, 1-5 parts of flame retardant, 1-3 parts of mildew-proof compound, 2-10 parts of cross-linking agent, 0.5-4 parts of coupling agent and 1-5 parts of catalyst; The preparation method of the mildew-proof composite is as follows: By weight, 12 to 18 parts of 1-bromomethylnaphthalene are added to 20 to 50 parts of methanol, and stirred at 70 to 80° C. for 1 to 3 minutes; then 50 to 70 parts of a 20 to 30 wt% polyhexamethylene guanidine phosphate aqueous solution are added at a rate of 1 to 2 mL / min, and stirring is continued for 8 to 15 minutes after the addition is completed, and the mixture is filtered and dried to obtain a modified guanidine salt; 0.5-0.8 parts of modified guanidine salt, 0.3-0.5 parts of pyraclostrobin, 1-2 parts of nano titanium dioxide and 0.5-1 parts of nano boron nitride are added to 10-30 parts of dioctyl terephthalate, subjected to ultrasonic treatment for 1-2 hours, centrifuged and dried to obtain the anti-mildew composite.
2. The sealant according to claim 1, characterized in that The modified white carbon black preparation method comprises the following steps: (1) By weight, 0.05-0.1 parts of sodium dodecyl sulfate and 1-3 parts of gas-phase SiO2 were added to an aqueous solution of 50-90 parts of ethanol, stirred evenly, and ultrasonicated for 0.5-1 hour, and then heated to 50-80°C. Then, 0.5-1 parts of γ-methacryloxypropyltrimethoxysilane were added dropwise to the reaction solution, and the mixture was reacted at a constant temperature for 2-4 hours, washed with ethanol, and centrifuged to obtain KH570-SiO2; (2) Place KH570-SiO2 in an ethanol solution, add 0.1-0.3 parts of hydroxy silicone oil and 1-2 parts of dibutyltin dilaurate dropwise thereto, stir at 10-40°C for 2-6 hours, wash with ethanol and centrifuge to obtain modified silica.
3. The sealant according to claim 1, characterized in that: The flame retardant is one or a mixture of two or more of Mg(OH)2 powder, modified Mg(OH)2 powder, triethyl phosphate, organic silicone powder, triphenyl phosphate, tributyl phosphate, ammonium polyphosphate and melamine.
4. The sealant according to claim 1, characterized in that: The plasticizer is one or a mixture of two or more of 201 methyl silicone oil, white oil, and epoxy soybean oil.
5. The sealant according to claim 1, characterized in that: The crosslinking agent is one or more of methyltributylacetoximine silane, vinyltributylacetoximine silane, methyltrimethoxysilane, ethyltrimethoxysilane and methyltriacetoxysilane.
6. The sealant according to claim 1, characterized in that: The coupling agent is one or two or a mixture of two or more of γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane.
7. The sealant according to claim 1, characterized in that: The catalyst is one or two or a mixture of two or more of dibutyltin dilaurate, dihexyltin dilaurate, dibutyltin diacetate, dihexyltin diacetate, isopropyl titanate and butyl titanate.
8. The method for preparing a sealant according to any one of claims 1 to 7, characterized in that: Including steps such as: S1 weighs 50-70 parts of 107 silicone rubber, 20-50 parts of plasticizer, 10-20 parts of modified white carbon black, 1-5 parts of flame retardant, 1-3 parts of mildew-proof compound, 0.5-4 parts of coupling agent, and 1-5 parts of catalyst, adds them to a kneader, stirs for 3-5 hours at 80-120°C and vacuum degree -0.06--0.1MPa, and then grinds to obtain powder; S2. After the powder obtained in step S1 is cooled to 30-60°C, the powder is added to a disperser, 2-10 parts of a cross-linking agent are added, and stirring is continued for 20-40 minutes under a vacuum degree of -0.06--0.1 MPa, and the sealant is obtained by discharging and packaging.
Citation Information
Patent Citations
Environment-friendly sealant and preparation method thereof
CN107686709A
Environmentally friendly sealant and preparation method thereof
CN108997945A
Modified white carbon black and preparation method thereof as well as silicone rubber
CN108559274A
Silicone weather-resistant flame-retardant sealant and preparation method thereof
CN112322250A